Integration and competition between transport and logistics businesses: Summary and conclusions - OECD; International Transport Forum (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2009)
The Round Table, chaired by Russell Pittman of the US Department of Justice, reviewed trends in horizontal and vertical integration in logistics businesses, maritime shipping, ports and rail freight transport and examined the circumstances in which integration might reduce the efficiency of the transport system. There are likely to be net benefits to society from such integration in competitive markets but if integration eliminates competition, market power might result in excessive prices, suboptimal investment and lower than optimal levels of service for the users of transport services. Options for sector specific regulators and competition authorities to manage the risks of market abuse were discussed and the adequacy of antitrust law and competition authorities to take remedial action should businesses exploit market power were assessed.
Keywords: 330